Crimes against nature: illegal industries and the global environment - Liddick, Don (Praeger, 2011)
The nature of the problem -- The traffic in garbage and hazardous wastes -- The illicit traffic in wildlife -- Illegal fishing -- Illegal logging -- Conclusion